Knowledge of Mothers' Behavioral Training About Oral Hygiene of Elementary School Children at RSGM Baiturrahmah - Sri Pandu Utami; Atikah Putri Sakinah (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background Parents need to know, how to teach and train their children to take care of their teeth from early age because because early age child have reached motor maturity followed by intellectual development. Parents who have low knowledge children's care tend to ignore and not support their children's dental health. Parents and children must work together to maintain good oral hygiene.It can be seen that poor parental attitudes generally reflect poor oral health in children and vice versa. Objectives: to describe mothers’ knowledge about oral hygiene attitudes and practices out how the role of mothers in maintaining children's teeth and to determine the health of children's teeth. Methods: using questionnaires and descriptive analysis of probability sampling approach by combining aspects of stratification and cluster sampling in the IKGA (Ilmu Kedokteran Gigi Anak) lab room, Baiturrahmah University, around 30 respondents were sampled in each place and randomly selected. Results: from the results of the study, it was found that mothers who graduated from school were 34.72% and mothers who graduated from diploma/bachelor were 65.28% of the population, 10 (35%) have only attended elementary school and 20 (65%) mothers who graduated. Conclusion: Mothers are less aware of dental disease prevention measures, the importance of brushing teeth, and visits to the dentist. Therefore, it is the responsibility of the government and health service providers to provide knowledge on oral health to mothers, because they are role models for their children.